SOCIAL AND PEDAGOGICAL FEATURES OF FORMATION OF MODERN ECONOMISTS’ PROFESSIONAL COMPETENCE - Siryk, Tatiana V. (Educological discourse, 2015)
The article deals with the social-pedagogic features of formation of professional competence of economists in modern conditions, the essence of the terms«competency»and «competence» from the point of view of different sciences is discovered, the conditions of today society are investigated and the main characteristics of young specialists, which are needed for modern employers are defined. The processes, that occur in European and world economics, and corresponding social and educational guidance in the system of higher education cause the forming of new strict requirements to the professional competence of modern specialists and the perfection of the process of their professional training.